Small-signal characterization and modelling of 55 nm SiGe BiCMOS HBT up to 325 GHz. (March 2017) - Deng, Marina; Quémerais, Thomas; Bouvot, Simon; Gloria, Daniel; Chevalier, Pascal; Lépilliet, Sylvie; Danneville, François; Dambrine, Gilles
Highlights: The SiGe HBT S-parameters from 250 MHz to 325 GHz are presented for the first time. Standard calibration and de-embedding techniques remained valid up to 325 GHz. A small-signal model was compared with measurements up to 325 GHz. Abstract: This paper presents a small-signal characterization work on a recently developed 55 nm SiGe BiCMOS technology from STMicroelectronics. The SiGe HBT from a prototype BiCMOS 55 nm process was investigated up to 325 GHz. The full S-parameters from DC to 325 GHz under multiple bias conditions are presented for the first time for a SiGe HBT. A usual and simple approach for the off-wafer calibration associated to an on-wafer de-embedding procedure was used and remained valid up to 325 GHz thanks to a size reduction of the test structures. The extracted 300/325 GHz fT /fMAX couple, reached at 14 mA/μm 2 collector density and 1.2 V collector-emitter voltage, was validated up to 325 GHz.